Genome-wide analysis of respiratory burst oxidase homolog gene family in pea (Pisum sativum L.) - Liu, Minmin; Zhang, Yu; Pan, Ting; Li, Yuanyuan; Hong, Youheng; Chen, Wenjie; Yang, Yao; Zhao, Gangjun; Shabala, Sergey; Yu, Min (Frontiers in Plant Science, 2023)
Plant respiratory burst oxidase homologs (RBOHs) are key enzymes regulating superoxide production, which is important for plant development and responses to biotic and abiotic stresses.This study aimed to characterize the RBOH gene family in pea (Pisum sativum). Seven PsRBOH genes were identified in the pea genome and were phylogenetically clustered into five groups.Collinearity analyses of the RBOHs identified four pairs of orthologs between pea and soybean.The gene structure analysis showed that the number of exons ranged from 6 to 16. Amino acid sequence alignment, conserved domain, and conserved motif analyses showed that all seven PsRBOHs had typical features of plant RBOHs. The expression patterns of PsRBOH genes in different tissues provided suggested their roles in plant growth and organ development. In addition, the expression levels of PsRBOH genes under different abiotic stresses were analyzed via reverse transcription-quantitative polymerase chain reaction (RT-qPCR). The results demonstrated that PsRBOH genes exhibited unique stress-response characteristics, which allowed for functional diversity in response to different abiotic stresses. Furthermore, four PsRBOHs had a high probability of localization in the plasma membrane, and PsRBOH6 was localized to the plasma membrane and endoplasmic reticulum. The results of this study provide valuable information for further functional analysis of pea RBOH genes and their role in plant adaptation to climate-driven environmental constraints.